Sports medicine and health science - Chengdu ti yu xue yuan (Elsevier B.V. on behalf of KeAI Communications Co. Ltd, 2019)
The purpose of the Sports Medicine and Health Science (SMHS) journal is to provide a scientific, merit-based, high-quality publication platform for all relevant biomedical studies worldwide with a primary focus on sports medicine, physical activity, and the exercise-related health sciences. The primary disciplines that are covered by SMHS include but are not limited to clinical sports medicine; orthopedics; preventive medicine; rehabilitation medicine; physical therapy; basic and translational sports sciences including exercise physiology, exercise biochemistry, exercise molecular biology, and exercise immunology; biomechanics; motor control and exercise neuroscience; exercise epidemiology, gerontology, and nutrition; and complementary and alternative medicine.
Keywords: Sports medicine : Periodicals; Medical sciences : Periodicals; Medical sciences; Sports medicine; Athletic Injuries; Sports Medicine